Synthesis of Recommendations From 25 Countries and 31 Oncology Societies: How to Navigate Through Covid-19 Labyrinth - Kamposioras, Konstantinos; Mauri, Davide; Papadimitriou, Konstantinos; Anthoney, Alan; Hindi, Nadia; Petricevic, Branka; Dambrosio, Mario; Valachis, Antonis; Kountourakis, Pantelis; Kopecky, Jindrich; Kuhar, Cvetka Grašič; Popovic, Lazar; et al. (Frontiers in Oncology, 2020)
Introduction Pandemic COVID-19 is an unexpected challenge for the oncological community, indicating potential detrimental effects on cancer patients. Our aim was to summarize the converging key points providing a general guidance in order to support decision making, pertaining to the oncologic care in the middle of a global outbreak. Methods We did an international online search in twenty five countries that have managed a surge in cancer patient numbers. We collected the recommendations from thirty one medical oncology societies. Results By synthesizing guidelines for a) oncology service delivery adjustments, b) general and specific treatment adaptations, and c) discrepancies from guidelines comparison, we present a clinical synopsis with the forty more crucial statements. A Covid-19 risk stratification base was also created in order to obtain a quick, objective patient assessment and a risk-benefit evaluation on a case-by-case basis. Conclusions In an attempt to face these complex needs and due to limited understanding of COVID-19, a variability of recommendations based on general epidemiological and infectious disease principles rather than definite cancer-related evidence has evolved. Additionally, the absence of an effective treatment or vaccine requires the development of cancer management guidance, capitalizing on comprehensive COVID-19 oncology experience globally.